Strategic Human Resource Management :an international perspective - Rees, Gary, 1962-; Smith, Paul, 1957- (2021)
"Whether you are studying at undergraduate or postgraduate level, our stellar team of expert authors will guide you through the key topics of human resource management from a strategic perspective. Starting with the fundamentals of each topic and progressing through to critical evaluation, the 3rd edition includes: even more international case studies from across Europe, Asia, Australia and the Middle East - which bring the theory and academic underpinning to life." -- provided by publisher.
Part 1: The organization, the organizational context and strategy -- 1: An introduction to the organization, its environment and human resource management -- 2: Human resource management through a strategic perspective -- 3: Concepts, practices and trends in SHRM -- 4: The added value debate -- Part 2: the functional aspects of HR -- 5: Recruitment and selection -- 6: Flexible working -- 7: Reward strategy and managing performance -- 8: Managing the employment relationship -- 9: Equality and diversity in the workplace -- 10: Developing employees and managers -- Part 3: SHRM and the 'bigger picture' -- 11: Organizational culture -- 12: Managing in a global context -- 13: The future of HR.
Previous edition: 2017.
Includes bibliographical references (pages 517-585) and index.
Keywords: Personnel management; Personnel management